Analysis of the Implementation of Minimum Service Standard Policies on Inpatient Service Performance in Hospitals: Literature Review - Yulya Lasmita; Wa Ode Salma; Jumakil; Nani Yuniar; Adius Kusnan; Hilda Harun (Journal of Health Science and Pharmacy, 2025)
Background: Minimum Service Standards (SPM) are mandatory policy instruments implemented in hospitals to ensure service quality, measurability, and patient safety. However, the application of SPM in inpatient units varies among hospitals due to differences in human resources, infrastructure availability, and operational mechanisms. These inconsistencies may affect service quality and overall hospital performance, indicating the need for a systematic review to evaluate the effectiveness of SPM implementation based on original research evidence. Objective: This study aims to analyze original research findings related to the implementation of SPM and Standard Inpatient Class (KRIS) policies and their association with inpatient service performance in hospitals. Methods: This study employed a Systematic Literature Review (SLR) guided by PRISMA. Relevant articles published between 2020 and 2025 were identified from Google Scholar, PubMed, Scopus, ResearchGate, and ScienceDirect using keywords related to SPM, KRIS policy, hospitals, policy implementation, and inpatient service performance. Results: The review indicates that SPM and KRIS implementation generally improves inpatient service performance, particularly patient satisfaction and compliance with service standards. Nevertheless, some studies reported discrepancies between SPM achievement and service quality, reflecting uneven implementation. KRIS success is influenced by facility readiness, human resource competence, and structural compliance, while challenges include infrastructure limitations and SOP adjustments. Conclusion: SPM and KRIS strengthen inpatient service performance, but optimal outcomes require adequate infrastructure, competent human resources, aligned SOPs, and strong policy support.